Has democratization reduced infant mortality in sub-Saharan Africa? Evidence from micro data - Masayuki Kudamatsu (Osaka University, Institute of Social and Economic Research (ISER), 2007)
Does democracy help babies survive in sub-Saharan Africa? By using retrospective fertility surveys conducted in 28 African countries, I compare the survival of infants born to the same mother before and after democratization to identify the effect of democracy. In measuring democracy, I adopt a theoretically motivated definition of democracy: universal suffrage and contested elections for executive office. I find that infant mortality falls by 1.8 percentage points, 18 percent of the sample mean, after democratization. The size of the reduction is larger for babies born to mothers from disadvantaged groups. I also find that the replacement of a chief executive by democratization is the driving force behind these results. Additional evidence suggests that improvements in public health service delivery, not an increase in affluence, are the key mechanism in which democratization has reduced infant mortality.
Additional information: The Ninth ISER-Moriguchi Prize (2007) Awarded Paper.
Keywords: 330; Demokratisierung; Kindersterblichkeit; Korrelation; Schätzung; Afrika südlich der Sahara